Between selection and inclusion in vocational education and training : contrasting Switzerland and Spain - Marhuenda Fluixá, Fernando [Verfasser]; Bonoli, Lorenzo [Verfasser] (My University, 2025)
“This article discusses inclusivness of Vocational Education and Training (VET) at Upper Secondary Education (USE). While inclusion has become a policy aim in compulsory education, it is not so clear that it is the case beyond post-16 education. In the case of VET, the demand of high quality standardized vocational qualifications challenges inclusion. The article addresses three different dimensions of inclusion: access to VET at USE, successfully achieving a qualification, and entering the labor market in a position according to the qualification achieved. We approach inclusion from a policy rather than a pedagogical perspective in section 2, and in section 3 our hypothesis about the inclusiveness of a school-based VET and a dual VET system are presented. In section 4 we choose Spain and Switzerland as examples of these systems, we show indicators, and we describe how both systems deal with the three dimensions of accessing, achieving a qualification and entering the labor market. The analysis concludes by stating that inclusion is particularly difficult because of the first dimension: it is in transition to VET in USE where both countries have more difficulties and could improve their inclusiveness. The problem is the same, but the reasons are different and these are explained in the text, addressing tensions between reputation and inclusiveness and the externalization of measures. Some considerations on comparative education also result from our analysis.” (authors’ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2 Übergänge; I 2.2.1 Westeuropa; 370; Berufsausbildung; Berufseinmündung; Inklusion; Spanien; Schweiz